1984
DOI: 10.1136/bmj.288.6422.975
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent bleeding from idiopathic ulceration of small bowel.

Abstract: Results of testing of specimens produced by transtracheal saline injection for 42 patients with community acquired pneumnonia No of patients Result of testing lower respiratory tract secretion* 22 Pneumococcal antigen positive: no pathogens on culture 13 Pneumococcal antigen negative: no pathogens on culture 4 Pneumococcal antigen positive: Str pneumoniae on culturet 2 Pneumococcal antigen not tested: no pathogens on culture 1 No specimen obtained * Pneumococcal antigen detected using countercurrent immunoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The condition itself may not be a distinct entity but merely embrace residual 'idiopathic' cases of enteric ulceration after other definitive aetiological types have been excluded. Thus a recent report describes two fatal cases of (multiple) simple ulceration in patients with severe heart disease, in whom intestinal ischaemia was thought to be involved (Glynn et al, 1984), whereas our patients were generally younger and had a less acute presentation.…”
Section: Discussionmentioning
confidence: 65%
“…The condition itself may not be a distinct entity but merely embrace residual 'idiopathic' cases of enteric ulceration after other definitive aetiological types have been excluded. Thus a recent report describes two fatal cases of (multiple) simple ulceration in patients with severe heart disease, in whom intestinal ischaemia was thought to be involved (Glynn et al, 1984), whereas our patients were generally younger and had a less acute presentation.…”
Section: Discussionmentioning
confidence: 65%
“…In contrast, the subsequent clinical course was very different between the two groups with respect to relapse and management of the disease. Before the recognition of NSAID enteropathy there were some descriptions of non-specific small intestinal ulcers, particularly during the 1960s, [3][4][5][6] and thiazides or potassium tablets were presumed to have contributed to their pathogenesis. 7 24 25 However, approximately 60% of the reported cases were thought to be unrelated to medications.…”
Section: Discussionmentioning
confidence: 99%
“…1 2 In the 1960s, cases of non-specific ulcers of the small intestine were reported in the literature. [3][4][5][6] Subsequently, it became evident that a proportion of nonspecific small intestinal ulcers were caused by thiazides, potassium tablets, 7 or non-steroidal anti-inflammatory drugs (NSAIDs). 8 9 In contrast, cases of unexplained chronic, non-specific small intestinal ulcers have been reported in the literature.…”
mentioning
confidence: 99%
“…Many of the cases described in the 1960s and 1970s were due to potassium chloride tablets (11)(12)(13)(14). Since the removal of these drugs from the market, the number of described cases has decreased (11), with fewer reports in the 1970s and 1980s (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and, to our knowledge, none in the 1990s. The possible etiology of these lesions remains unclear.…”
Section: Ida Caused By Idopathic Small Bowel Ulcerationmentioning
confidence: 99%
“…The possible etiology of these lesions remains unclear. Glynn et al (20) described two cases of small bowel ulcers associated with cardiovascular disease with bad prognosis, and raised the hypothesis that ischemic damages could be the cause of such lesions. The Mayo Clinic reported that approximately 19% of patients had concomitant cardiovascular disease but an ischemic cause was considered unlikely (11).…”
Section: Ida Caused By Idopathic Small Bowel Ulcerationmentioning
confidence: 99%